A percepção de alunos de cursos de graduação sobre o tempo de dedicação em atividades desenvolvidas por meio de aprendizagem baseada em problemas com apoio de Tecnologias de Informação e Comunicação - Palhardi, André Luiz (2019)
The present work aims to deepen the knowledge regarding the interactions of the students when in activities oriented by the Problem Based Learning (PBL) methodology in isolated activities of common disciplines of the curricular matrix of the courses of Bachelor in Engineering. Due to the increasing adoption of active learning methodologies in formal and informal teaching environments, it is sought to make possible its adoption, since these approaches have advantages and disadvantages like any other. Through some researchers it is noticed that one of the biggest barriers to the adoption of the PBL is the time of dedication of the students to act in the activities foreseen in the methodology. It is explored, in the practical approach of this work, the application of a PBL activity, with support of Information and Communication Technologies - TICs and it is sought to extract from the student his perception of the time of dedication in said activity. This approach takes on a hybrid context in the process and innovates in this aspect, since the majority of the interventions in PBL occur integrally. As the theoretical basis of the study, it is deepened in the knowledge related to the PBL method, to the TICs, the perception and phenomenological approach to qualitative research.